Akulturasi Budaya Lokal dan Agama Dalam Grebeg Apem di Kabupaten Jombang, Provinsi Jawa Timur - Isti, Desfanti Meliana; Kurnia, Heri (Universitas Cokroaminoto Yogyakarta, 2022)
Grebeg Apem is a symbol of the relationship between ancestors, nature and each other. This is a ritual pattern that contains local culture and Islamic values. So do not be surprised if the implementation of Grebeg Apem is still related to local culture which is then assimilated into Islamic values by Wali Songo. In addition, this study will explain how the relationship between Nyadran and religious values. A qualitative research approach was applied to answer research questions. These results show a very strong relationship. Religious values with the Grebeg Apem tradition include the value of worship aimed at worshiping Allah, the second value of muamalah aims so that the Islamic community and others do not differentiate between each other, the third value of hospitality aims to keep brothers and sisters unbroken and more harmonious and peaceful.